In vivo promoter engineering in plants: Are we ready?. (December 2018) - Pandiarajan, Ramakrishnan; Grover, Anil
Highlights: Promoters/Cis regulatory elements (CREs) can serve as excellent targets for crop improvement via genome editing. Ability to manipulate plant's double strand break repair machinery using genome editing has made in vivo promoter engineering (IPE) feasible. Improved tolerance to biotic and abiotic stress as well alteration of plant architecture has been achieved using IPE. Data generated from high throughput techniques that investigate DNA-protein interactions in conjunction with bioinformatics packages will immensely augment IPE. Crops developed using IPE are transgene free. Abstract: Engineering plant promoter sequence for optimal expression of a gene has been a long standing goal for plant scientists. In recent times, Sequence Specific Nucleases (SSNs) like CRISPR/Cas9 are enabling researchers to achieve this goal, in vivo in the genome. It is well known that SSNs have met with unprecedented success in rapid transgene free crop improvement largely by targeting the coding sequence. Here, we discuss the strategies being employed by plant scientists in targeting SSNs to non-coding promoter regions/Cis Regulatory Elements (CRE). We collectively refer all such endeavors as in vivo promoter engineering (IPE). We further classify the IPE efforts into CRE addition, CRE deletion/disruption, promoter swap/insertion and targeted promoter polymorphism. Till date, IPE has proven useful in altering plant architecture in tomato, developing resistance against Xanthomonas sp in rice and citrus, and engineering drought tolerance in maize. However it is quite challenging to achieve predictable changes in gene expression using IPE at this point. In future years, data generated from high throughput techniques to investigate non coding genome may immensely augment the efforts in this direction. As IPE does not involve addition of the transgene for modifying crop traits, it will be relatively more conducive to public acceptance in crop improvement programs.